2018
DOI: 10.2136/sssaj2017.05.0160
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Facile Method for Characterizing Shrinkage Geometry along the Granitic Soil Profile

Abstract: A simple and facile approach was proposed for measuring the anisotropic shrinkage. Subsidence was dominant for soils in the loose and aggregated structure. Horizontal shrinkage was predominant for soils with the horizontal arrangement of plate particles The shrinkage behavior of granite soils was controlled by clay content and pore structure. Soil volume change resulting from frequent drying–wetting cycles leads to severe erosion and landslides in granite regions. Limited attempts have been made to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 44 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Therefore, this method is relatively simple and effective. This method of adding cracks to the model is possible mainly due to the low content of hydrophilic minerals in the weathered granite soil and minimal swelling when encountering water (Wei et al, 2018; Zhang & Tang, 2013). Kaolinite is the main clay mineral in weathered granite soil, with a relative content of more than 92%, followed by illite, with a relative content of 4%–8%, indicating that the wetting effect on weathered granite soil is relatively small (Wei, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this method is relatively simple and effective. This method of adding cracks to the model is possible mainly due to the low content of hydrophilic minerals in the weathered granite soil and minimal swelling when encountering water (Wei et al, 2018; Zhang & Tang, 2013). Kaolinite is the main clay mineral in weathered granite soil, with a relative content of more than 92%, followed by illite, with a relative content of 4%–8%, indicating that the wetting effect on weathered granite soil is relatively small (Wei, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The county has a typical subtropical monsoon climate with annual precipitation of approximately 1450 to 1600 mm and an annual average temperature of approximately 15.5 to 16.7 C. This rainy climate and mountainous terrain have led to the active development of collapsing gullies, and there are 1102 Benggangs in Tongcheng County. The zonal soil, derived from weathered granite and classified as an Ultisol (US Soil Taxonomy), is locally called red soil (Wei et al, 2018). In the study area, two typical Benggang slopes with complete soil profiles, TC1 and TC2, were selected (Figure A1).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…For a better understanding of the high-steep slope of a collapsing wall and the mechanism of collapsing erosion, the engineering characteristics and preferential flows have also been investigated for the profile of the collapsing wall. Some researchers analyzed the spatial variations of shear strength and hydraulic properties in collapsing gullies and evaluated their effects on the collapsing erosion mechanism [14,[18][19][20]. Additionally, researchers have also investigated the variations of chemical composition and physical properties with soil depth in the collapsing gullies and found that the contents of gravel and sand increase while the amount of sesquioxides decreases with an increase of soil depth [21,22].…”
Section: Introductionmentioning
confidence: 99%